Daun Timbul dalam Ekspresi Karya Seni Rupa - Sumarjaya Putra, I Made Adi; Sujana, I Wayan; Supriyatini, Sri (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
This MBKM Independent Project report, bearing the title "Leaves Timbul in the Expression of Fine Artwork" departs from an embossed tree located in the studio of Kaki Bisma Batan Timbul which inspired the writer to create works of art. The problem is how to visualize the leaves appearing in each work. In visualizing the author uses methods and techniques obtained from the MBKM process. The purpose and benefits are to develop the writer's creativity in expressing imaginary forms as well as images/photos that are edited according to the needs of the author in the work process, the author chooses I Ketut Budiana himself who is a favorite artist and uses his creation method which includes several stages, namely, reflection, research. foundation, exploration, experimentation, execution, completion. From this process the author produced 6 works entitled: 1) "Life", 2) "Science", 3) "Mother Earth". 4) "Ngangon Kebo", 5) "Faithful Animals", 6) "Sidakarya Mask". It can be concluded that the author created works based on his interest in embossed leaves, with ideas originating from phenomena captured in the Kaki Bisma Batan Timbul studio and reading reference sources from the internet. campus, To be realized in the form of 2 dimensions and 3 dimensions From all these processes, it is expected to find identity in the work.